Proteasome beta-4 subunit contributes to the development of melanoma and is regulated by miR-148b - Xiaodong Zhang; Di Lin; Yueqin Lin; Hongqing Chen; Minghua Zou; Shan Zhong; Xuefeng Yi; Siqi Han (Tumor Biology)
The proteasome beta-4 subunit is required for the assembly of 20S proteasome complex, forming a pivotal component for the ubiquitin–proteasome system. Emerging evidence indicates that proteasome beta-4 subunit may be involved in underlying progression and mechanisms of malignancies. However, the role of proteasome beta-4 subunit in melanoma is currently unknown. Here, we reported that proteasome beta-4 subunit was markedly upregulated in human melanoma tissues and cells, compared with normal skin samples. High proteasome beta-4 subunit levels were significantly associated with poor overall survival in patients with melanoma. Proteasome beta-4 subunit knockdown strongly decreased melanoma cell growth in vitro and in vivo. We further identified miR-148b as a negative regulator of proteasome beta-4 subunit. Enforced expression of miR-148b resulted in vitro growth inhibition of melanoma cells, whereas this inhibition was further abolished by enforced expression of proteasome beta-4 subunit. Our findings, for the first time, indicated that the miR-148b/proteasome beta-4 subunit axis contributed to the development of melanoma, revealing novel therapeutic targets for the treatment of melanoma.